Communication Ability and Verbal Communication Apprehension of Senior High School Adolescents With Intellectual Disability: Research Based on Picture Exchange Communication System (PECS) and Measure of Elementary Communication Apprehension (MECA) - Happy Cahyani Sunusi; Chr. Hari Soetjiningsih; A. Ign. Kristijanto (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
The purpose of this study are: firstly, to determine the effect of Picture Exchange Communication System (PECS) on the verbal communication skills of senior high school adolescent with intellectual disability; secondly, to determine the verbal communication apprehension in of senior high school adolescents with intellectual disability before and after PECS treatment; thirdly, to determine the difference verbal communication apprehension of senior high school adolescents with intellectual disability as revealed by sexes. Experimental design for verbal communication skills used Analysis of Covariance with Randomized Completely Block Design (RCBD) based on six phases of pre- and post-test. Senior high school student from class X-XII (n = 13) became sample of this research. Questionnaire used was in the form of the Measure of Elementary Commu-nication Apprehension (MECA) questionnaire while the data analysis used Analysis Cova-riance for verbal communication skill, t-paired test for verbal communication apprehension, and verbal communication apprehension between sex were analyzed by t-test with a 5% level of significance. The results showed that: (1) PECS can improve the verbal communication skills between phases of PECS with the effectiveness as follows: 105.14%, 18.49%, and 43.11%; (2) PECS have not affected the verbal communication apprehension of senior high school adolescents with intellectual disability (tcale = - 0.305 < ttable = - 1.771); and (3) There is no significant differences in verbal communication apprehension of senior high school adolescents with intellectual disability based on sexes (tcale = 0.232 < ttable = 2.342).